Prognostic role of hs-CRP before and after Percutaneous Coronary Intervention in Patients with Stable Angina Pectoris (University Heart Journal, 2022)
Background and Objectives: Myocardial injury after percutaneous coronary intervention (PCI) occurs frequently and it is associated with an adverse clinical outcome. Mechanical factors have been implicated in this complication and the role of inflammation has not yet been clearly determined. We evaluated the effect of an inflammatory response during PCI on periprocedural myocardial injury.Subjects and Methods: This prospective observational study was conducted in the Department of Cardiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh over a period between July’2012 to June’2013. A total of 200 patients studied who underwent elective coronary stenting. For the exclusion of mechanical injury to the myocardium, we excluded those patients who developed complications during PCI. The inflammatory response to PCI was calculated as the difference between the peak postprocedural hs-CRP level and the preprocedural hs-CRP level . We divided the patients according to the median value of hs- CRP: Group I 3 mg/L.Results: Postprocedural TnI elevation was were observed in 72 (36%) patients. The baseline clinical and angiographic characteristics were not difference between the two groups. The incidence of any TnI elevations was higher in the Group II than that in Group I (19.8% vs 42.6%, respectively, p